Analysis Study About Service Quality Improvement of PT Putra Indonusa Garment Konveksi - Santoso, Aditya Nugroho; Aldianto, Leo (Journal of Business and Management, 2012)
Growth of industrial garment is advancing rapidly at this time. The stability of economic and political make many new companies springing up. As a company in the field of garment manufacturing services, PT. Putra Indonosa Garment Konveksi should be able to read customer characteristics and analyze customer satisfaction level based on quality of service This research assesses the response of sample visitors with 130 respondents from their business partner through analysis of customer satisfaction of the attributes of the gap between perceptions and expectations of our customers and using importance-performance analysis. This study how measure how far the difference between expectation and perception of customers in PT. Putra Indonosa Garment Konveksi. This process is analyzed by descriptive analysis. The conclusion of this research is most of customer was not satisfied with the performance of PT. Putra Indonosa Garment Konveksi and its performance does not match with customer’s expectations. Service quality attributes that are not in accordance with customer expectation is reliability, responsiveness, empathy and tangible. In reliability dimension, the customer did not get the promised service, then in responsiveness dimension, the company doesn’t have willingness to help customers, and last in empathy dimension the company doesn’t have the customer’s best interest at heart.this research recommends that PT. Putra Indonosa Garment Konveksi need to hire experienced employees, provided service as promises, provides a solution if there is a complaint, deliver product according costumer order, willingness to help costumer problem, gives the best service.Key words: Service Quality, Gap Analysis between Perception and Expectation, Importance – Performance Analysis